Legislative provision of regulation in the field of land use and protection - Dorosh, Y.; Barvinskyi, A.; Novakovska, I.; Avramchuk, B.; Stetsiuk, M. (Land Management, Cadastre and Land Monitoring, 2021)
The current state of legislative support in the field of land use and protection is analyzed. It is established that the legal framework in this area, especially with regard to the powers of executive authorities and local governments, is characterized by a lack of system, clarity and specificity, which is a significant obstacle to the practical implementation of land protection measures. It is proved that the improvement of legislative support in the research area should be carried out by systematizing the relevant powers of executive authorities and local governments, filling existing gaps, eliminating unnecessary layers and conflicts in laws and regulations. The need to eliminate the dispersion and duplication of powers of executive authorities and local governments in the field of land use and protection to improve the efficiency of their activities in this area by making appropriate changes and additions to legislation. To this end, it is proposed to concentrate norms on similar powers of different ministries, services, inspections, local governments and local administrations in this area in one legislative act, and to strengthen state control over land use and protection, regardless of category and form of ownership, to restore the State Land Inspectorate. Ukraine with the granting of appropriate powers. Key words: land use and protection, legislative acts, powers of executive bodies and local self-government.